Focus on monitoring and control of complex supply systems - Robin Delabays; Laurent Pagnier; Benjamin Schäfer; Melvyn Tyloo; Dirk Witthaut (Journal of Physics: Complexity)
The ongoing rapid transformation of our energy supply challenges the operation and stability of electric power grids and other supply networks. This focus issue comprises new ideas and concepts in the monitoring and control of complex networks to address these challenges.